Epidemija samomorov? - Remec, Meta (Prispevki za novejšo zgodovino, 2023)
The following article analyses the issue of suicide in Slovenia from the first statistical analyses that also covered the territory inhabited by Slovenians in the second half of the 19th century until the end of the 1960s, when the relevant statistical data and public pressure, also resulting from the incorrect and distorted interpretations of these data, prompted the contemporaneous socialist authorities to actively address the problem. Based on statistical data and their interpretations as well as on the reports from the police, the State Security Service, and the press, the article outlines the discourses of the authorities, the profession, and the media. It shows how the phenomenon of suicide was perceived by the different segments of society and reveals the various interpretations of the reasons for the increasing suicide rates in each of the periods under consideration. It also describes how suicide data became a means of manipulation and retaliation against political opponents as well as a tool for pointing out the culprits for the alleged blunders of society.
Keywords: mladi; samomori; samomorilni količnik; socializem